Prevalence and severity of menopause symptoms among perimenopausal and postmenopausal women aged 30-49 years in Gulele sub-city of Addis Ababa, Ethiopia - Engida Yisma; Natnael Eshetu; Stephanie Ly; Berhanu Dessalegn (BMC, 2017)
Abstract Background Menopause is a natural phenomenon occurring as women approach middle-age. It is characterized by declining of ovarian function and onset of the last menstrual period and subsequent 12-month cessation of menstruation. Due to a growing aging population and longer life expectancies, sub-Saharan African women will spend a significant portion of their lives in postmenopause. Menopausal symptom research has been primarily conducted on Caucasian women from high-income countries. Understanding menopause symptom prevalence and perceptions among diverse women in Ethiopia will better inform reproductive health care. Methods We conducted a multi-stage, cross-sectional study on 226 perimenopausal and postmenopausal women aged 30-49 years in Gulele sub-city of Addis Ababa, Ethiopia. Data on socio-demographic characteristics, menopausal status and an 11-item Menopause Rating Scale (MRS) were collected using interviewer-administered questionnaire. Statistical analyses consisted of descriptive data and chi-squared analyses. Results Study participants were 40.4 ± 5.9 years, on average, with the majority married, educated at secondary school level, and comprised different ethnicities and wealth tertiles. The most prevalent types of menopausal symptoms reported from the MRS were from somatic subscale (65.9%) while psychological (46.0%) and urogenital subscale symptoms (30.5%) were also prevalent. The most commonly reported individual symptoms were: hot flushes (65.9% (95% CI: 59.4%-72.1%)), difficulty falling asleep (49.6% (95% CI: 42.9%-56.3%)), depressive mood (46.0% (95% CI: 39.4%-52.8%)), irritability (45.1% (95% CI: 38.5%-51.9%)), and anxiety (39.8% (95% CI: 33.4%-46.5%)). Each of the somatic, psychological, and urogenital MRS subscale scores were higher among postmenopausal women compared to perimenopausal women. Women self-reported differing severity levels of symptoms with high severity reported in 8.4% of total MRS, 1.3% of somatic, 10.6% of psychological, and 8.4% of urogenital scales. Conclusions Our study provides the first presentation of menopausal symptoms among perimenopausal and postmenopausal women in the Gulele sub-city of Addis Ababa, Ethiopia. We capture the prevalence of menopausal symptoms experienced as well as self-rated severity through the MRS. Our findings reflect menopausal symptoms in our specific study population and have been found to be consistent with previous international research.